A gene transfer event suggests a long-term partnership between eustigmatophyte algae and a novel lineage of endosymbiotic bacteria - Yurchenko, Tatiana; Ševčíková, Tereza; Přibyl, Pavel; El Karkouri, Khalid; Klimeš, Vladimír; Amaral, Raquel; Zbránková, Veronika; Kim, Eunsoo; Raoult, Didier; Santos, Lilia M A; Eliáš, Marek (The ISME journal, 2018)
Rickettsiales are obligate intracellular bacteria originally found in metazoans, but more recently recognized as widespread endosymbionts of various protists. One genus was detected also in several green algae, but reports on rickettsialean endosymbionts in other algal groups are lacking. Here we show that several distantly related eustigmatophytes (coccoid algae belonging to Ochrophyta, Stramenopiles) are infected by Candidatus Phycorickettsia gen. nov., a new member of the family Rickettsiaceae. The genome sequence of Ca. Phycorickettsia trachydisci sp. nov., an endosymbiont of Trachydiscus minutus CCALA 838, revealed genomic features (size, GC content, number of genes) typical for other Rickettsiales, but some unusual aspects of the gene content were noted. Specifically, Phycorickettsia lacks genes for several components of the respiration chain, haem biosynthesis pathway, or c-di-GMP-based signalling. On the other hand, it uniquely harbours a six-gene operon of enigmatic function that we recently reported from plastid genomes of two distantly related eustigmatophytes and from various non-rickettsialean bacteria. Strikingly, the eustigmatophyte operon is closely related to the one from Phycorickettsia, suggesting a gene transfer event between the endosymbiont and host lineages in early eustigmatophyte evolution. We hypothesize an important role of the operon in the physiology of Phycorickettsia infection and a long-term eustigmatophyte-Phycorickettsia coexistence.
Keywords: Rickettsiaceae; Stramenopiles; genomika; Symbiosis; symbióza; Gene Transfer, Horizontal; Heterokontophyta; operon; Operon; přenos genů horizontální; Genomics